Land-based versus water-based walking programs in elderly women with knee osteoarthritis: preliminary results of a randomized clinical trial - Arrieiro, Arthur N.; Mendonça, Vanessa A.; Fonseca, Sueli F.; Santos, Jousielle M.; Ribeiro, Vanessa C. G.; Amorim, Mateus R.; Leopoldino, Amanda A. O.; Lacerda, Ana C. R. (Brazilian Journal of Health and Biomedical Sciences, 2019)
Introduction: Knee osteoarthritis (kOA) is a chronic degenerative disorder. Aerobic exercise programs have been effective treatments to reduce symptoms in kOA. However, studies comparing land- and water-based interventions did not control for the intensity of exercise programs. Objectives: Investigate the effects of walking programs with a controlled progressive workload in water compared to land in terms of pain, functional and physical performance, and quality of life in elderly women with kOA. Materials and Methods: The walking training programs were divided into two groups: 1) land-based aerobic training (LB); and 2) water-based aerobic training (WB). Each training session was divided into three phases: 1 – Warm-up (5 minutes): stretching exercises; 2 - Training (30 to 55 minutes): walking at target heart rate; 3 – Cool-down (5 minutes). Sixteen elderly women with kOA underwent assessments of functional performance using the six-minute walk test (6MWT) and the stair test (ST), while physical performance, maximum oxygen consumption (VO- 2max) and anaerobic threshold (AT) were determined during a progressive test. kOA was assessed by the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and quality of life was assessed using the Medical Outcomes Study 36-Item Short Form Health Survey (SF-36). All parameters were reevaluated after 12 weeks of aerobic training that consisted of walking (duration: 30-55 min.; intensity: 72-82% of maximal heart rate). Results: No significant difference between the LB and WB groups was found. There was a reduction in self-reported pain (by WOMAC), increased performance in the 6MWT and ST, increased VO2max and VO2max corresponding to AT and improved quality of life (by SF-36) in both groups after training compared with before intervention. Conclusion: Land-based aerobic training was as effective as its water-based equivalent in clinical, physical and functional parameters in elderly women with knee OA. Keywords: Osteoarthritis of knee; Elderly; Aerobic training.